2022
DOI: 10.1177/17588359221112486
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of local therapy to metastatic foci in nasopharyngeal carcinoma: large-cohort strictly-matched retrospective study

Abstract: Background: Studies of local therapy (LT) to metastatic foci from nasopharyngeal carcinoma (NPC) are inconsistent and controversial. Here, we aimed to explore the survival benefit of LT directed at metastatic foci from NPC. Methods: A retrospective analysis was conducted in NPC patients with liver, lung, and/or bone metastases. The postmetastatic overall survival (OS) rate was analyzed using the Kaplan–Meier method and compared by the log-rank test. Multivariate analysis was performed using the Cox hazard mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The study showed that these patients received more than 6 cycles of chemotherapy would have better survival and prognosis 24 . But after when these patients had been treated by palliative chemotherapy plus locoregional radiotherapy, further local radiotherapy to bone metastases would not significantly improve survival 25–27 . If performed radiotherapy to metastatic bones, the radiation dose should give radical dose rather than palliative dose 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that these patients received more than 6 cycles of chemotherapy would have better survival and prognosis 24 . But after when these patients had been treated by palliative chemotherapy plus locoregional radiotherapy, further local radiotherapy to bone metastases would not significantly improve survival 25–27 . If performed radiotherapy to metastatic bones, the radiation dose should give radical dose rather than palliative dose 28 .…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 The survival of patients with metastatic NPC (mNPC) is poor, with a median overall survival (OS) of 12-30 months despite multidisciplinary therapies. 1,6,7 Systemic chemotherapy with or without immunotherapy remains the main treatment for mNPC. Local treatment is also recommended for selected patients with limited metastases or a low tumor burden.…”
Section: Introductionmentioning
confidence: 99%
“…Local treatment is also recommended for selected patients with limited metastases or a low tumor burden 8,9 . Moreover, several studies have demonstrated that patients with mNPC can benefit from local radiotherapy, either alone or in combination with chemotherapy 7,8,10–12 . However, the optimal radiation modality for metastases remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is a frequent malignancy in Southeast Asia, especially in Guangdong Province of China. Radiotherapy is a fundamental treatment for NPC, with a 5‐year overall survival (OS) of 68.2%–87.4% for nonmetastatic NPC 1–3 . However, 5%–15% of patients develop residual or recurrent disease at the primary site 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is a fundamental treatment for NPC, with a 5-year overall survival (OS) of 68.2%-87.4% for nonmetastatic NPC. [1][2][3] However, 5%-15% of patients develop residual or recurrent disease at the primary site. [4][5][6] Surgery can directly resect primary failure and avoid sequelae caused by re-irradiation and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%